2016
DOI: 10.3389/fphar.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Soft TCPTP Agonism—Novel Target to Rescue Airway Epithelial Integrity by Exogenous Spermidine

Abstract: A reparative approach of disrupted epithelium in obstructive airway diseases, namely asthma and chronic obstructive pulmonary disease (COPD), may afford protection and long-lasting results compared to conventional therapies, e.g., corticosteroids or immunosuppressant drugs. Here, we propose the polyamine spermidine as a novel therapeutic agent in airways diseases, based on a recently identified mode of action: T-cell protein tyrosine phosphatase (TCPTP) agonism. It may include and surpass single-inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…After 24 h starvation, the cells were pretreated with SPD (Sigma S2501, spermidine trihydrochloride), 100 nM, 24 h. The starvation step was useful to reduce the endogenous polyamine pool so to better highlight the effect of 100 nM exogenous SPD pre-treatment. This subμmolar dose was selected on the basis of previous literature hints that indicate a narrow useful dosage window in which addition of exogenous SPD may support cell homeostatic activities by increasing the unbound pool without exerting inflammation or apoptosis promoting effects [32]. Previous work from our group showed that 1-10 μmolar doses instead promote chondrocyte terminal differentiation [33], in keeping with previous observations of high SPD levels in the extracellular matrix of the ossifying cartilage [34].…”
Section: Culture and Treatment Of Chondrocyte Primary Culturesmentioning
confidence: 54%
“…After 24 h starvation, the cells were pretreated with SPD (Sigma S2501, spermidine trihydrochloride), 100 nM, 24 h. The starvation step was useful to reduce the endogenous polyamine pool so to better highlight the effect of 100 nM exogenous SPD pre-treatment. This subμmolar dose was selected on the basis of previous literature hints that indicate a narrow useful dosage window in which addition of exogenous SPD may support cell homeostatic activities by increasing the unbound pool without exerting inflammation or apoptosis promoting effects [32]. Previous work from our group showed that 1-10 μmolar doses instead promote chondrocyte terminal differentiation [33], in keeping with previous observations of high SPD levels in the extracellular matrix of the ossifying cartilage [34].…”
Section: Culture and Treatment Of Chondrocyte Primary Culturesmentioning
confidence: 54%
“…Spermine compacts DNA more actively than spermidine 52 . Furthermore, inside the cells spermidine is primarily complexed to anionic molecules and macromolecules (phospholipids of the cell membrane, ATP, RNA, DNA wrapped with histones) and only a fraction of the intracellular content represents the “free pool” 53 . Slight variation of this pool is achieved by treatment of the cells with low- µmolar/sub-µmolar amounts of spermidine, that have been shown to promote anti-inflammatory effects via triggering of T-cell protein tyrosine phosphatase (TCPTP) 54 or autophagy 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Slight variation of this pool is achieved by treatment of the cells with low- µmolar/sub-µmolar amounts of spermidine, that have been shown to promote anti-inflammatory effects via triggering of T-cell protein tyrosine phosphatase (TCPTP) 54 or autophagy 55 . TCPTP is a phosphatase that exerts an anti-inflammatory role being able to down-regulate multiple signaling transduction pathways in the cells, acting at multiple levels 53 . An in vitro high throughput assay identified spermidine (at the same concentration used in the present work) and other 5 small molecules among 64280 potential candidates screened to tease out the best selective TCPTP agonists 56 .…”
Section: Discussionmentioning
confidence: 99%
“…36 We saw higher levels of spermidine, a product of ORN that plays a role in the regulation of cell proliferation and nucleic acid synthesis. 37,38 Previous studies report higher levels of ARG in muscles of COPD patients, but not in arterial blood. 12,13 In stable patients with moderate-to-severe COPD, endogenous ARG and CIT production is upregulated but no difference in whole body NO production was detectable (ARG-to-CIT flux).…”
Section: Amino Acids Involved In Nitrogen Removalmentioning
confidence: 96%